Slovak validation of the Levels of self-criticism scale - Halamová, Julia (Psihološka obzorja (Ljubljana), 2018)
Severe self-criticism is one of the underlying psychological factors which most influence susceptibility to psychopathology and its persistence. This study verifies the psychometric features and factor structure of the Slovak version of the Levels of SelfCriticism Scale. It entails the use of descriptive analysis, reliability analysis, validity analysis, and IRT confirmatory factor analysis. As opposed to the English version with two dimensions (Internalized Self-Criticism and Comparative Self-Criticism) using classical factor analysis, the Slovak translation has three factors (Internalized Self-Criticism, Unfavourable Comparison with Others and Favourable Comparison with Others) exploiting more advanced IRT factor analysis. It is important to explore this question in more detail in future, especially because the proposed three-dimensional structure is not very meaningful from the purely theoretical perspective. The Levels of Self-Criticism Scale appears to have acceptable level of reliability and validity. Therefore, we recommend using this instrument to assess the levels of self-criticism in the English and Slovak versions.
Keywords: factor analysis; faktorska analiza; item response theory; Lestvica stopenj samokritičnosti; Levels of self-criticism scale LOSC; measurement; merjenje; psihometrija; psychometrics; samokritičnost; self-criticism; sestava testa; teorija odgovora na postavko; test construction; test reliability; test validity; veljavnost; zanesljivost